The Role Of Society In Controlling Juvenile Delinquency - Sharma, Rashima (Trinity Law Review, 2021)
One of the most important issues in today's society is juvenile delinquency. It's virtually a by product of modern times' fast urbanisation and industry. The family pattern has been influenced by  the social conditions connected with these two processes. As a result, an environment conducive  to the emergence of adolescent delinquency has emerged. A huge number of people moving from  rural areas to the cities or living in slums in cities are found to be highly vulnerable to this process. Delinquency is a rare occurrence. The term "delinquency" refers to a person's behaviour that  deviates from the normal flow of social life. A juvenile delinquent is a young person under the age  of 18 who engages in behaviour that could endanger society or oneself.
Keywords: Controlling Juvenile Delinquency; delinquency